Peran pajak sebagai instrumen kebijakan fiskal dalam upaya mewujudkan pembangunan ekonomi Nasional - Fauziyah, Nurul (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of taxes as a fiscal policy instrument in efforts to realize national economic development. Taxes themselves have a very important role for every country, one of which is Indonesia. Tax is defined as a taxpayer’s contribution to the State that is owed to either an individual or an entity that is coercive based on applicable law, without receiving direct compensation and is used for state needs for the greatest welfare of the people. This research is a library research approach using qualitative methods that focus on phenomena that occur in society. The aim of the research is to find out the role of taxes as a fiscal policy instrument in efforts to realize national economic development.